PEMBERDAYAAN UMKM DI PERMUKIMAN VERTIKAL: STRATEGI DAN PRAKTIK PENGELOLAAN BISNIS DARI NOL DI RUSUN JATINEGARA KAUM - Siti sunawati; Ade Fajar; Indah Suwarni (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2025)
Managing micro, small and medium enterprises (MSMEs) from scratch is a challenge thatrequires the preparation of the right business strategy, perseverance, and adaptability to marketconditions. This paper aims to provide practical guidance and identify key success factors forMSMEs through seminars featuringsuccessful MSME entrepreneurs who have buit theirbusinesses from scratch. Careful business planning, product innovation, the use of digitaltechnology, and the ability to adapt to market changes are important elements in MSMEmanagement. In addition, social network support and the ability to manage finances effectivelyare also the key to business sustainability. In this journal, the author will provide practicalguidance in the form of tips and tricks that can be applied by MSME business people. Such asstarting from market needs, building a strong brand, and investing in self-development. This studyis expected to help entrepreneurs minimize risks and enhance their chances of successfullymanaging MSMEs from their inception to expansion.